Relationship Of Nutritional Status With The Occurrence Of Anemia In Pregnant Women - Asdinar; Sri Eka Juniarli (Jurnal Life Birth, 2018)
Nutritional Status is a measure of success in fulfilling nutrition for pregnant women. Nutritional status is also defined as the health status produced by the balance between nutrient requirements and inputs. Pregnant mother's nutrition is a healthy and balanced food that must be consumed by the mother during her pregnancy, with a portion of two meals a person who is not pregnant. As for this study is to determine the relationship of nutritional status with the incidence of anemia in pregnant women that is everything that is known by the mother pregnancy including definition, causes, effects, efforts, and others. The research design used in the cross-sectional study was carried out in August in the work area, the population is all 696 pregnant women using non-probability sampling consecutive sampling technique with 46 samples. The results of the study are the nutritional status of pregnant women. It showed that respondents who had a chronic energy deficiency were 12 people (26.1%) compared to no chronic energy shortages by 34 respondents (73.9%) in pregnant women. Anemic respondents with the characteristics of anemia and no anemia had the same number, every 23 people (50%) in pregnant women in the work area. Chi-Square statistical test results showed that the value of P = 0.008 (P = <0.05) it is proven that there is a relationship between nutritional status and the incidence of anemia in pregnant women. This study concludes that there is a relationship between nutritional status and the incidence of anemia in pregnant women. This research suggests that the results of this study can be material information and input for students and all related institutions to determine the relationship of nutritional status with the incidence of anemia in pregnant women.